(untitled) (Fiep Bulletin - online, 2024)
Introduction: Monitoring training loads is a powerful tool to achieve victory in team sports, represented by Thor’s hammer metaphor. Objective: This scientific article discusses the importance of monitoring training loads in team sports for optimizing athletic performance and preventing injuries. Methods: The article presents a review of the literature on monitoring training loads in team sports, focusing on advancements in the field, including internal and external load monitoring, monitoring tools, and monitoring devices. Results: The review emphasizes the importance of implementing multifaceted athlete monitoring systems to ensure that the correct training dose is given at the right time, increase physical conditioning, and decrease fatigue. Conclusion: The article concludes that a scientific approach to load monitoring is essential for optimizing athletic performance and preventing injuries. Comprehensive monitoring should address mechanical, physiological, psychological, social, behavioral, and cognitive factors. Therefore, it is essential that coaches understand the importance of monitoring training loads and include it in their training programs, as a powerful weapon to increase performance in competitions.